"The influence of traditional english teaching and learning methods, supportead by the emotional intelligence over the english teaching and learning process of Bet-el Elementary School, David-Chiriquí, 2011" - Espinosa, Nabyll (UDELAS, 2011)
Most of the teacherse make use of traditional english teaching methods; students make a great effort to learn with old english learning techniques. There is something wrong with them. Intellect is the essential basis for education, which is made up of teaching and learning.